THE ROLE OF PARALINGUISTIC FEATURES IN THE ANALYSIS OF MULTI MODAL ARGUMENTATION THE ROLE OF PARALINGUISTIC FEATURES IN THE ANALYSIS OF MULTI MODAL ARGUMENTATION THE ROLE OF PARALINGUISTIC FEATURES IN THE ANALYSIS OF MULTI MODAL ARGUMENTATION - Kišiček, Gabrijela (2014)
This paper aims to contribute to our understanding of multi-modal argumentation by examining the role of paralinguistic features in persuasive messages. The importance of paralinguistic features in non-verbal communication, especially in recognizing emotion, is perhaps already beyond doubt. Standard analyses of advertisements, moreover, already assign a key role to visuals in understanding, reconstructing and assessing the argument. However, the role of other non-verbal content is often found neglected. Vocalic or paralinguistic features refer to, amongst others, accent, emphasis, vocal quality, pitch, rate, temporal structure, and pause as either contributing to the meaning of verbal communication, or as self-standing meaningful entities (Hickson, Stacks and Moore, 2004). Empirical studies (e.g. Kramer (1977, 1978, Frick, 1985, Zuckerman and Miyake 1993, Neuman and Strack, 2000) suggest that both voice cues (e.g. pitch, intensity, voice quality) and speech cues (speech rate, pause etc.) are important factors in audiences’ assessments of speaker credibility—operationalized, for instance, as ratings of competence and dominance vs. likability and benevolence, (Zuckerman and Driver, 1989). Generally, speakers may indicate by prosodic means the information a listener should pay particular attention to. Some studies have also sought to determine a connection between vocals qualities and audience attitude change. Burgoon et al. (1990) conclude that specific vocal signs, such as variation of pitch, faster tempo and higher intensity (louder speech), positively correlate with persuasive effect, the perceived credibility of the speaker, and audience attitude change. On this background, I present reconstructions of TV commercials that take into account verbal, visual and paralinguistic components. Because paralinguistic features are here especially relevant to reinforcing the argumentation, they should not without further reasons be neglected in argumentation analysis. Highlighting the importance of paralinguistic features for analyses of argumentative discourse, I also discuss whether such features lend reinforcement merely by reinforcing the speaker’s ethos or if they can also be understood as a new, or at any rate different component of the argumentation.
ENG